Report of the 24th meeting on signal transduction 2021 - Schirmer, Bastian; Giehl, Klaudia; Hieke-Kubatzky, Katharina (International journal of molecular sciences, 2022)
The annual meeting “Signal Transduction - Receptors, Mediators and Genes” of the Signal Transduction Society (STS) is an interdisciplinary conference which is open to all scientists sharing a common interest in the elucidation of the signaling pathways mediating physiological or pathological processes in the health and disease of humans, animals, plants, fungi, prokaryotes, and protists. The 24th meeting on signal transduction was held from 15 to 17 November 2021 in Weimar, Germany. As usual, keynote presentations by invited scientists introduced the respective workshops, and were followed by speakers chosen from the submitted abstracts. A special workshop focused on “Target Identification and Interaction”. Ample time was reserved for the discussion of the presented data during the workshops. Unfortunately, due to restrictions owing to the SARS-CoV-2 pandemic, the poster sessions - and thus intensive scientific discussions at the posters - were not possible. In this report, we provide a concise summary of the various workshops and further aspects of the scientific program.
Gesehen am 05.04.2022